Bifunctional In Situ Polymerized Interface for Stable LAGP‐Based Lithium Metal Batteries. Issue 10 (23rd March 2021) - Zhang, Shengnan; Zeng, Zhen; Zhai, Wei; Hou, Guangmei; Chen, Lina; Ci, Lijie
Abstract: All‐solid‐state lithium metal batteries (ASSLMBs) have attracted intensive research attention since their incomparable energy density and the further advance of ASSLMBs is severely dependent on the development of solid electrolytes. Unfortunately, as one of the most studied solid electrolytes, the practical applications of (NASICON)‐type Li1.5 Al0.5 Ge0.5 P3 O12 (LAGP) electrolyte is hindered by not only its inferior interfacial contact with electrodes but also its undesirable instability toward Li metal anodes. In this work, a bifunctional in situ formed poly(vinylene carbonate) (PVCA)‐based buffer layer is introduced between the LAGP electrolyte and the metallic Li anode to improve interface compatibility and the electrolyte stability. The improved interface contact between LAGP and electrodes and the enhanced stability of LAGP enable ASSLMBs with excellent electrochemical performance. The Li/LAGP/Li symmetric cell with the PVCA‐based interlayer can maintain a low overpotential of 80 mV for 800 h at 0.05 mA cm –2 . Inspiringly, the as‐assembled ASSLMBs with LiFePO4 as the cathode also present excellent cyclic stability with a high initial discharge capacity of 150 mAh g –1 at 0.5 C and superior capacity retention of 96% after 200 cycles. Abstract : A bifunctional ionically conductive poly(vinylene carbonate) (PVCA)‐based buffer layer is introduced between Li1.5 Al0.5 Ge0.5 P3 O12 (LAGP) electrolyte and Li anode, which not only acts as a barricade to isolate LAGP pellet from Li metal, but also forms a LiF‐enriched solid electrolyte interphase (SEI) to promote the uniform deposition of Li ion on the Li surface and improve the cycle life of LAGP‐based full cells significantly.